TEACHING THE PAST PARTICIPLE THROUGH DRILLING TECHNIQUE - Agung Pranoto Kadiatmaja (STAI Ali bin Abi Thalib Surabaya, 2022)
The study conducted at The Mushlih Institute (TMI) English Development Centre in Surabaya was to find out whether or not the drilling technique influenced TOEFL Preparation Takers' structure and written expression comprehension. The focus is on teaching past participles in the students' practice. The research included sixty students in the TOEFL Preparation class from international undergraduate and postgraduate programs. Twelve students were chosen as the experimental group's sample and twelve students as the control group. Cluster random sampling was used to collect the sample. The writer employed the match t-test to analyze the data while carrying out the research. The finding of this study has proved that the drilling strategy is influential and productive for teaching TOEFL Paper-based Test Structure: Past Participle to TOEFL Preparation Test Takers at TMI English Development Centre Surabaya.